2010
DOI: 10.1088/0957-4484/21/13/134013
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale patterning induced strain redistribution in ultrathin strained Si layers on oxide

Abstract: We present a comparative study of the influence of the thickness on the strain behavior upon nanoscale patterning of ultrathin strained Si layers directly on oxide. The strained layers were grown on a SiGe virtual substrate and transferred onto a SiO(2)/Si substrate using wafer bonding and hydrogen ion induced exfoliation. The post-patterning strain was evaluated using UV micro-Raman spectroscopy for thin (20 nm) and thick (60 nm) nanostructures with lateral dimensions in the range of 80-400 nm. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…Thicker layers can be obtained by additional homoepitaxial growth without significant relaxation of the strain. For a 0.6% initial strain it has been found that the strain can be preserved during the subsequent homo‐epitaxial growth up to a thickness of 60 nm …”
Section: Strain Distribution In Silicon‐on‐insulator (Soi) Structuresmentioning
confidence: 99%
“…Thicker layers can be obtained by additional homoepitaxial growth without significant relaxation of the strain. For a 0.6% initial strain it has been found that the strain can be preserved during the subsequent homo‐epitaxial growth up to a thickness of 60 nm …”
Section: Strain Distribution In Silicon‐on‐insulator (Soi) Structuresmentioning
confidence: 99%
“…In previous work, SOI-structures have been characterised by Micro-beam Raman Spectroscopy [7], X-ray diffraction (XRD) [7]; cross-sectional high resolution transmission electron microscopy [8], white beam X-ray topography technique [9] and high-resolution nano-beam electron diffraction [10]. Here we report characterisation of SOI wafer structures by a coherent X-ray diffractive imaging method, which produces real-space images of the defects with a resolution potentially reaching tens of nanometres.…”
Section: Soi Fabrication Techniquesmentioning
confidence: 99%
“…Recently, it was demonstrated that ultrathin, globally strained silicon layers (nanomembranes) are the material of choice to generate strained Si nanowires using top-down nanofabrication processes [7,10,11]. Interestingly, upon nanoscale patterning of biaxial strained nanomembranes-a crucial step in the fabrication of strained nanowires-the formation of free surfaces induces a local relaxation of strain due to rearrangement of lattice atoms near the newly formed edges [10,[12][13][14][15][16]. In general, the extent of this phenomenon depends on dimension and geometry [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%